2021
DOI: 10.25077/jsfk.8.1.53-59.2021
|View full text |Cite
|
Sign up to set email alerts
|

Uji Aktivitas Antioksidan dan Daya Hambat Enzim Tirosinase Ekstrak Etanol Azolla filiculoides Lam.

Abstract: Azolla (Azolla filiculoides Lam.) merupakan tanaman paku air dari famili Azollaceae. Azolla filiculoides digunakan sebagai pakan alami dengan ketersediaannya melimpah di alam yang belum termanfaatkan secara optimal. Tanaman ini dapat bersimbiosis dengan Cyanobacteria. Azolla memiliki senyawa bioaktif yang berfungsi sebagai antioksidan dan inhibitor tirosinase. Tujuan dari penelitian ini adalah untuk menguji aktivitas antioksidan menggunakan metode DPPH (2.2-difenil 1-pikrihidrasil ) dan daya hambat tirosinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…The ability of flavonoids as antioxidant compounds is due to their properties as good acceptors against free radicals. Phenolic and flavonoid compounds from plants have the ability to act as antioxidants because they are able to scavenge reactive oxygen species (ROS) which produce free radicals (Prasetyo, 2021). From the results of the identification of samples with ethanol solvent which contain secondary metabolite compounds in the form of flavonoids and the results of the Tukey statistical test, it can be concluded that the ethanol extract and ascorbic acid as a positive control are not significantly different and the ethanol solvent is not significantly different from the water solvent.…”
Section: Dpph Methods Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of flavonoids as antioxidant compounds is due to their properties as good acceptors against free radicals. Phenolic and flavonoid compounds from plants have the ability to act as antioxidants because they are able to scavenge reactive oxygen species (ROS) which produce free radicals (Prasetyo, 2021). From the results of the identification of samples with ethanol solvent which contain secondary metabolite compounds in the form of flavonoids and the results of the Tukey statistical test, it can be concluded that the ethanol extract and ascorbic acid as a positive control are not significantly different and the ethanol solvent is not significantly different from the water solvent.…”
Section: Dpph Methods Antioxidant Activitymentioning
confidence: 99%
“…The standard used in the calculation of MDA levels is tetramethoxypropane (TMP). Standard TMP in acidic conditions can be hydrolyzed to produce semiacetal and methanol, the hemiacetal formed will then decompose into methanol and aldehyde which can react with TBA (Prasetyo, 2021;Wresdiyati et al, 2002). The resulting linear regression equation for measuring the standard curve is y = 0.0406x -0.0133 with a value of r = 0.9961.…”
Section: Malondialdehyde Inhibitor (Tba-mda)mentioning
confidence: 99%
“…Senyawa steroid memiliki aktivitas antitirosinase dengan mekanisme mengikat beberapa situs dari enzim tersebut kecuali situs katalitik. Sedangkan, kuinon memiliki aktivitas antitirosinase yang mekanismenya berkaitan dengan gugus fungsi yang melekat pada kerangkanya (Prasetyo, 2021).…”
Section: Gambar 1 Daun M Speciosa Korthunclassified
“…External sources of free radical generation include stress, ozone radiation, pollution, pesticides, and industrial chemicals, all of which can harm molecules, proteins, lipids, RNA, and DNA in the body [1,2]. Free radicals can cause cellular oxidative damage, which diminishes the body's defense system and makes a significant contribution to diseases such as diabetes, hypercholesterolemia, cancer, arthritis, arteriosclerosis, degenerative neuro-diseases, and premature aging [1,2]. As a result, antioxidants are required by our bodies to protect us from free radical damage According to Halliwell in [3], antioxidants are substances that inhibit, prevent, and completely remove oxidative damage to target molecules.…”
Section: Introductionmentioning
confidence: 99%